2013
DOI: 10.1002/jpln.201200628
|View full text |Cite
|
Sign up to set email alerts
|

Rate of soil‐aggregate formation under different organic matter amendments—a short‐term incubation experiment

Abstract: To improve soil structure and take advantage of several accompanying ecological benefits, it is necessary to understand the underlying processes of aggregate dynamics in soils. Our objective was to quantify macroaggregate (> 250 μm) rebuilding in soils from loess (Haplic Luvisol) with different initial soil organic C (SOC) contents and different amendments of organic matter (OM) in a short term incubation experiment. Two soils differing in C content and sampled at 0–5 and 5–25 cm soil depths were incubated aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(16 citation statements)
references
References 36 publications
1
15
0
Order By: Relevance
“…As a result, the substantial amounts of microbial products and other organics are accumulated and serve to stabilize the macroaggregates, so increasing the MWD (Table 2). This is in accordance with the findings of several studies that addition of recently available organic materials led to higher microbial activity and more organic compounds serving as binding agents for macroaggregate formation (Le Guillou et al, 2012;Andruschkewitsch et al, 2014). It is worthy to note that large macroaggregate was the only aggregate fraction responsible for the apparent increase in total amino sugar concentrations with elevated manure applications, indicating a low efficiency of microbial C sequestration by high manuring.…”
Section: Amino Sugarssupporting
confidence: 87%
See 1 more Smart Citation
“…As a result, the substantial amounts of microbial products and other organics are accumulated and serve to stabilize the macroaggregates, so increasing the MWD (Table 2). This is in accordance with the findings of several studies that addition of recently available organic materials led to higher microbial activity and more organic compounds serving as binding agents for macroaggregate formation (Le Guillou et al, 2012;Andruschkewitsch et al, 2014). It is worthy to note that large macroaggregate was the only aggregate fraction responsible for the apparent increase in total amino sugar concentrations with elevated manure applications, indicating a low efficiency of microbial C sequestration by high manuring.…”
Section: Amino Sugarssupporting
confidence: 87%
“…This indicates that amount of manure application strongly influenced SOM quality with respect to microbial residues. It was suggested that macroaggregates are the most dynamic (Six et al, 2000) and they are oversaturated with SOC with only a smaller amount of the added organic matter being stabilized for longer periods within macroaggregates in the soil (Andruschkewitsch et al, 2014). Therefore, greater proportions of amino sugars in SOC in macroaggregate fraction are important for the SOM pool's capacity to function as an active nutrient sink and source reservoir.…”
Section: Indicative Significance Of Amino Sugar Proportion In Soc Witmentioning
confidence: 99%
“…Macro-aggregate formation is a rapid process driven by the amount of carbon input and fungal activity (De Gryze et al, 2005). Macroaggregates can develop within 7 days in a loess soil, containing many times more SOC than the parent material, but are relatively unstable so act as a carbon source for microbial decomposition (Andruschkewitsch et al, 2014). The degree of aggregation depends on the size distribution of organo-mineral associations and their chemical characteristics (Christensen, 2002).…”
Section: Aggregate Scalementioning
confidence: 99%
“…Several researchers found that the input of organic material is positively related to the formation of aggregates (Christensen, ). The aggregate disruption upon crop residue incorporation is postulated to be compensated by the fast reformation of aggregates (Andruschkewitsch et al ., ) caused by an increase in microbial activity and microbially derived binding agents (Mikha & Rice, ). However, we could not detect an increase in C mic concentration and CO 2 emission (as indicator for microbial activity) for the treatments with residue incorporation.…”
Section: Discussionmentioning
confidence: 99%